Nursing Diagnoses in People with Digestive Stoma and their Association with Sociodemographic and Clinical Factors - Moya‐Muñoz, Noelia; Capilla‐Díaz, Concepción; Labella‐Rodríguez, Marta; Gálvez‐Cano, Judit; Sánchez‐Crisol, Inmaculada; Hueso‐Montoro, César (International journal of nursing knowledge, 2019)
PURPOSE To determine nursing diagnoses in people with a digestive stoma and their relationship with sociodemographic and clinical variables. METHOD A cross‐sectional descriptive study of 102 subjects in the General Surgery Unit of a first‐level hospital (Granada, Spain) was conducted. Data were collected on the presence of nursing diagnoses, sociodemographic and clinical variables. RESULTS NANDA‐I: “Deficient knowledge (00126)” and “Readiness for enhanced health management (00162)” were present in the entire sample studied. The period of care (postoperative vs. follow‐up) was the most common significant variable among diagnoses. CONCLUSIONS This work contributes to the determination of NANDA‐I diagnoses in people with digestive stomas. IMPLICATIONS FOR NURSING PRACTICE The results provide a guide to help nursing professionals develop individual care plans.